Settler solidarities as praxis: understanding 'granny activism' beyond the highly-visible. (2nd September 2016) - Chazan, May
Abstract: Across Canada, the Raging Grannies are renowned for appearing, invited or not, in spaces not typically open to older women, with outrageous 'Granny' costumes and satirical songs. A movement of predominantly non-Indigenous, settler women, the Raging Grannies regularly work in diverse activist coalitions in pursuit of social and environmental justice; many are seeking to ally themselves with contemporary Indigenous movements. However, while analyses have so far focused on their highly visible and iconic activist strategies, their solidarity-building efforts remain under-examined. Based on focus groups, interviews, and participant observation carried out in 2014–2015, this paper probes why and how Raging Grannies are building alliances with Indigenous movements in Canada. What emerges is an important tension. While many view their irreverent and theatrical strategies as quintessential to their 'Granny Activism, ' such tactics were unanimously deemed inappropriate for engaging with Indigenous movements. Underpinned by reflections on their own settler histories, feelings of outrage at ongoing and state-sanctioned colonial practices, fears of inadvertently reproducing colonial relations, and a sense of interconnected futures with Canada's First Peoples, they sought different, less-visible ways of practicing their solidarities. Many chose to attend rallies dressed in their everyday clothes, provide resources to Indigenous-led protests, invite Indigenous activists to speak at their gatherings, and work through their churches to redress past harm. Their solidarity efforts incorporated small acts, often pivoting around individual members' personal connections. This article thus depicts the Raging Grannies as more diverse in their practices than typically recognized. It also addresses an important gap in scholarship on older women's roles in solidarity movements. Finally, it extends existing scholarship on solidarity-building, suggesting that how solidarity is understood cannot be disconnected from how it is practiced, and thus demonstrating how solidarity can be relational, performative, and contingent.